A family of crisis in a dissipative Fermi accelerator model - Leonel, Edson D.; de Carvalho, R. Egydio (Elsevier B.V., 2007)
The Fermi accelerator model is studied in the framework of inelastic collisions. The dynamics of this problem is obtained by use of a two-dimensional nonlinear area-contracting map. We consider that the collisions of the particle with both periodically time varying and fixed walls are inelastic. We have shown that the dissipation destroys the mixed phase space structure of the nondissipative case and in special, we have obtained and characterized in this problem a family of two damping coefficients for which a boundary crisis occurs. (c) 2006 Elsevier B.V. All rights reserved.